El viento sabe nuestros nombres: winning short story of the Arturo Agüero Chaves Literary Contest, 2025 - Trejos Molina , Fiorella (2025)
The Wind Knows Our Names, by Fiorella Trejos Molina, winner of the 2025 Arturo Agüero Chaves Literary Contest in the short story category, recreates the mystery of Cedrices de Concepción, a village lost in the mist of the Western mountains. Through the characters Fabiola, Antonio, and Tatiana, the author builds an atmosphere of magical realism where time stands still and reality blends with myth. The story reflects on identity, memory, and destiny, exploring the longing to escape and the weight of origin as both condemnation and belonging.